2014
DOI: 10.1186/1749-7221-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of nerve transfer for restoration of shoulder and elbow function in upper brachial plexus injury

Abstract: BackgroundPurpose of this study was to evaluate the functional outcome of spinal accessory to suprascapular nerve transfer (XI-SSN) done for restoration of shoulder function and partial transfer of ulnar nerve to the motor branch to the biceps muscle for the recovery of elbow flexion (Oberlin transfer).MethodsThis is a prospective study involving 15 consecutive cases of upper plexus injury seen between January 2004 and December 2005. The average age of patients was 35.6 yrs (15–52 yrs). The injury-surgery inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 25 publications
6
46
1
3
Order By: Relevance
“…This might be either lower repair capacity or greater preoperative damage [18]. Contrastively, Venkatramani et al [23] suggested that the patient's age should not be a criterion for denying treating, and good results are also expected as they achieved good results in two patients in early 50s after nerve transfer. Similarly, a better prognosis was reported in this study with intervals between 6 and 10 months.…”
Section: Discussionmentioning
confidence: 99%
“…This might be either lower repair capacity or greater preoperative damage [18]. Contrastively, Venkatramani et al [23] suggested that the patient's age should not be a criterion for denying treating, and good results are also expected as they achieved good results in two patients in early 50s after nerve transfer. Similarly, a better prognosis was reported in this study with intervals between 6 and 10 months.…”
Section: Discussionmentioning
confidence: 99%
“…Elbow flexion, shoulder abduction, external rotation, and extension strength were assessed by Medical Research Council scale, with scores ranging from 0 (no evidence of contractility) to 5 (full range of motion against gravity with full resistance). The shoulder abduction and external rotation were classified based on the scale of Narakas [12,15] with minor modifications.…”
Section: Surgical Techniquementioning
confidence: 99%
“…It consists of neurotization of a fascicle of the ulnar nerve to a motor branch of the musculocutaneous nerve that heads towards the biceps. Excellent clinical results have been confirmed by different authors (13,26,27,33,35-39). Our experience with this type of neurotization has also been very good: in most cases, we have achieved a biceps of at least grade 3, which could be given more potential through possible transfer of the flexion-pronation musculature (Steindler).…”
Section: Diagnostic Methodsmentioning
confidence: 52%